Functions of non-standard English in fictional texts - Ziyovuddinova, Mahliyo Zuxriddin qizi (The Lingua Spectrum, 2026)
This study examines several functions of non-standard English in fictional texts, focusing on how these linguistic choices contribute to character development, thematic expression, and reader engagement. Personality of characters, their social background can be identified through their speech patterns. In addition, the use of non-standard English varieties reinforce the themes like tradition, cultural identity linking characters with their regional background. Moreover, non-standard language can create strong bonds between the characters and readers. Through a qualitative analysis and literary-linguistic approach, this research highlights the usage and functions of non-standard language within fiction. The analysis integrates textual data and case studies to present a comprehensive view of the non-standard language usage in literature. The paper focuses on a detailed analysis of “The Catcher in the Rye”, written by J.D. Salinger. The protagonist’s speech demonstrates how the author employs non-standard language to achieve specific literary objectives, including authenticity and realism. The findings show how non-standard language operates as an integral component of narrative meaning-making.